Influence of the electrical interface properties on the rheological behavior of sonicated soy lecithin dispersions - Alvarez, M.A. (2007)
A significant effect, on the rheological behavior, due to the electrical properties of vesicles formed from concentrated soy lecithin dispersions have been studied in this work. The rheopectic behavior of concentrated soy lecithin dispersions (120, 150, 180, 210 and 240 g L−1) prepared by swelling–light sonication–freezing–unfreezing procedure is studied and it is specially emphasized on the transition under steady shear from lamellar phase of planar sheets to closed structures as multilamellar vesicles. Samples have been exposed to a different number of sonication cycles (from 0 to 100) and the changes in the hysteresis loop area, the apparent viscosity and the electrophoretic mobility have been studied. When the number of sonication cycles increases, the size and number of bilayers of these multilamellar vesicles decrease and therefore the total number of the vesicles and the volume fraction occupied by them show an increase. © 2007 Elsevier Inc. All rights reserved